Is phôtistêrion a constantinopolitan Neologism? - Voicu, Sever J. (Augustinianum, 2012)
The earliest instance of φωτιστήριον « baptistery » in Antioch appears in the year 517, in a Syriac gloss to one of Severus’s homilies, perhaps in connection with his pastoral policies. Even if φωτιστήριον was formed according to same pattern as βαπτιστήριον, both nouns seem independent. John Chrysostom and an Antiochian Pseudo-Chrysostom do not mention at all the baptistery, but only the font (κολυμβήϑρα). The evidence indicates that during the 5th century φωτιστήριον was almost exclusively used in Constantinople and might have been created there. Some texts indicate that the word might have been the preferred name for the baptistery of a « cathedral » church, at least in Constantinople.